Nilai Signifikansi Cagar Budaya Hotel Inna Bali, Jalan Veteran Denpasar - Ida Ayu Diah Paramitha; I Wayan Kastawan; - Widiastuti (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2017)
This article explores the importance of Inna Bali Hotel, an historically significant colonial legacy of Denpasar city. In examining this Hotel as a built form for conservation, it discusses 3 main issues, namely: i) historical substantial meanings and values held by this hotel; ii) cross comparison between each meaning and values; and iii) the development of a conservation strategy for Inna Bali Hotel. The first issue was studied in terms of aesthetical, historical, social, and scientific aspects. Each aspect was measured in its accordance with the Indonesian Law Number 11, Year 2010 in regard to Cultural Heritage. When each of these four aspects were compared, the study indicated that historical aspect had been the most determining factor that leads to an urgent need to conserve the Inna Bali Hotel. This study subsequently developed a conservation strategy for every single built form exists on the Hotel's site. In implementing this strategy, this research further suggests that Inna Bali Hotel should indeed have relevant standard operating procedures governing every taken conservation activity. The whole study was carried out using qualitative research method, in which data collection was done by conducting on site observation and in depth interviews. Keywords: values, significance, cultural heritage, conservation